Implementasi Simulasi Ekspor Sebagai Media Pembelajaran Bisnis Internasional: Studi Kasus Produk Verward - Fadlillah Ramadhan; Wildan Fathil Padil; Dava Indira Dandy; Rizal Mustofa; Noval Wijaya; Bilal Arfiansyah (PENG: Jurnal Ekonomi dan Manajemen, 2025)
This study aims to analyze the implementation of a simulated export of a local t-shirt brand, Verward, to Japan by Management students. The simulation was conducted as part of experiential learning in the International Business course. A descriptive qualitative approach with a case study method was employed. Data were collected through communication records, shipping documentation, and confirmation of product receipt from the buyer in Japan. The results indicate that students were able to execute the export process in a real-world setting, including product selection, cross-border communication, international delivery, and transaction finalization. Key challenges faced included time zone differences, buyer trust, and understanding export procedures. However, these obstacles were addressed through effective communication strategies and teamwork. This simulation provided practical insight into small-scale export processes and enhanced students' readiness to engage in global business activities. The study recommends integrating export simulations into international business education as a method of experiential learning.